Chromosome Translocations, Gene Fusions, and Their Molecular Consequences in Pleomorphic Salivary Gland Adenomas - Stenman, Göran; Fehr, Andre; Skálová, Alena; Vander Poorten, Vincent; Hellquist, Henrik; Mikkelsen, Lauge Hjorth; Saba, Nabil F; Guntinas-Lichius, Orlando; Chiesa-Estomba, Carlos Miguel; Andersson, Mattias K; Ferlito, Alfio (Biomedicines, 2022)
Salivary gland tumors are a heterogeneous group of tumors originating from the major and minor salivary glands. The pleomorphic adenoma (PA), which is the most common subtype, is a benign lesion showing a remarkable morphologic diversity and that, upon recurrence or malignant transformation, can cause significant clinical problems. Cytogenetic studies of >500 PAs have revealed a complex and recurrent pattern of chromosome rearrangements. In this review, we discuss the specificity and frequency of these rearrangements and their molecular/clinical consequences. The genomic hallmark of PA is translocations with breakpoints in 8q12 and 12q13-15 resulting in gene fusions involving the transcription factor genes PLAG1 and HMGA2. Until recently, the association between these two oncogenic drivers was obscure. Studies of the Silver−Russel syndrome, a growth retardation condition infrequently caused by mutations in IGF2/HMGA2/PLAG1, have provided new clues to the understanding of the molecular pathogenesis of PA. These studies have demonstrated that HMGA2 is an upstream regulator of PLAG1 and that HMGA2 regulates the expression of IGF2 via PLAG1. This provides a novel explanation for the 8q12/12q13-15 aberrations in PA and identifies IGF2 as a major oncogenic driver and therapeutic target in PA. These studies have important diagnostic and therapeutic implications for patients with PA.
Keywords: chromosome 8q12; chromosome translocation; gene fusion; IGF2; HMGA2; PLAG1; therapeutic target; chromosome 12q13-15; pleomorphic adenoma; diagnostic biomarker